TECHNOLOGY FOR THE DEVELOPMENT OF STUDENTS’ MORALITY IN THE INFORMED EDUCATIONAL SYSTEM - Turaev Khahramon Nortojievich (Galaxy International Interdisciplinary Research Journal, 2023)
The article provides explanations and suggestions about the technology of developing students’ spirituality in the informational education system.